Microstructure and properties of SiC particle reinforced AA7075 composites by friction stir processing - Yuhan Duan; Yuehui Dang; Shuang Yi; Xianming Cao; Yu Cao; Zejun Chen (Journal of Materials Research and Technology)
In this study, friction stir processing (FSP) was used to successfully prepare SiC particle-reinforced aluminum matrix composites. The effects of SiC particle volume fraction on microstructure and mechanical properties were investigated using scanning electron microscopy, electron backscattering diffraction, tensile testing, and impact experiments. The results showed that the composites had good microstructures and mechanical properties when the volume fraction of SiC particles was 5%; in this case, the SiC particles were uniformly distributed inside the basis material with the minimum grain size. The uniform distribution of SiC particles transferred loads efficiently during impact, absorbing a significant amount of energy. This causes crack deflection and delays the fracture process, allowing the material to withstand higher impact loads while maintaining excellent impact toughness, with a maximum impact load and impact energy of 4.83 kN and 6780 mJ, respectively. However, the addition of 10% SiC particles in the composite caused agglomeration, forming defects that increased the likelihood of crack initiation and propagation, reducing the composite's performance.